NLRP1 restricts butyrate producing commensals to exacerbate inflammatory bowel disease - Corr, Sinead (My University, 2018)
Anti-microbial signaling pathways are normally triggered by innate immune receptors when detecting pathogenic microbes to provide protective immunity. Here we show that the inflammasome sensor Nlrp1 aggravates DSS-induced experimental mouse colitis by limiting beneficial, butyrate-producing Clostridiales in the gut. The colitis-protective effects of Nlrp1 deficiency are thus reversed by vancomycin treatment, but recapitulated with butyrate supplementation in wild-type mice. Moreover, an activating mutation in Nlrp1a increases IL-18 and IFNγ production, and decreases colonic butyrate to exacerbate colitis. We also show that, in patients with ulcerative colitis, increased NLRP1 in inflamed regions of the colon is associated with increased IFN-γ. In this context, NLRP1, IL-18 or IFN-γ expression negatively correlates with the abundance of Clostridiales in human rectal mucosal biopsies. Our data identify the NLRP1 inflammasome to be a key negative regulator of protective, butyrate-producing commensals, which therefore promotes inflammatory bowel disease.
PUBLISHED
Keywords: vancomycin treatment; Anti-microbial signaling pathways; detecting pathogenic microbes; vancomycin treatment; Anti-microbial signaling pathways; detecting pathogenic microbes; Immunology, Inflammation & Infection